Design and Construct A beam Profile of Near IR Laser Based on CCD Camera - Al-Ani, Ayad A; Ahmed, Mohammed S; Yousif, Muna S (Al-Nahrain Journal of Science, 2018)
One of many applications of Lasers is the beam profile. For some Lasers and applications this may only be necessary during the design and fabrication phase of the Laser. The aim of the research is to design and construct a Laser beam profile based on CCD camera. The system have been constructed on analyzing in the near infrared (NIR) Laser beams as the CCD silicon chip can be exploited in this region of the electromagnetic spectrum. The results show the successfulness of the profile in displaying proper Laser images. Also, care must be taken to avoid over exposing the CCD camera. Finally, stability of the imaging system is of great important.